2018
DOI: 10.1038/s41388-018-0385-y
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analysis identifies different transcriptomic types and developmental trajectories of primary melanomas

Abstract: Recent studies revealed trajectories of mutational events in early melanomagenesis, but the accompanying changes in gene expression are far less understood. Therefore, we performed a comprehensive RNA-seq analysis of laser-microdissected melanocytic nevi (n = 23) and primary melanoma samples (n = 57) and characterized the molecular mechanisms of early melanoma development. Using self-organizing maps, unsupervised clustering, and analysis of pseudotime (PT) dynamics to identify evolutionary trajectories, we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 50 publications
4
96
0
Order By: Relevance
“…We assigned all genes within these regions to the respective state and further processed them in analogy to gene sets that provided GSZ-values for each sample [see also Ref. ( 29 ) for details]. Heatmap presentations were generated by standard R-functions including hierarchical clustering options.…”
Section: Methodsmentioning
confidence: 99%
“…We assigned all genes within these regions to the respective state and further processed them in analogy to gene sets that provided GSZ-values for each sample [see also Ref. ( 29 ) for details]. Heatmap presentations were generated by standard R-functions including hierarchical clustering options.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, to analyze pri-miR-29 expression during melanomagenesis we performed RNA sequencing on four wildtype BRAF human melanocyte cell lines (Hermes1, Hermes2, Hermes3A, and Hermes4B) and five human melanoma cell lines (WM35, 1205Lu, WM164, SKMel28 and WM793) harboring the oncogenic BRAF V600E mutation. In addition, we interrogated pri-miR-29 expression in a publicly available RNAseq dataset (Kunz et al 2018) containing 23 nevi and 57 primary melanomas. In agreement with our observations, we found that there was a trend towards increased pri-miR-29b1~a expression in melanoma cell lines and primary melanomas compared to melanocyte cell lines and nevi, respectively ( Figure 3E and 3F).…”
Section: The Mapk Pathway Regulates Mir-29 Expression In Human Melanomentioning
confidence: 99%
“…It is thought that bypass from a senescence program contributes to the malignant transformation of benign nevi, but the mechanism of this process remains only partly understood. Recently, gene expression profiling of benign nevi and melanomas characterized two transcriptomic types of melanocytic nevi and primary melanomas (Kunz et al, 2018). The two melanoma subtypes were associated with a high versus low rate of NRAS mutation and harbored gene expression signatures for BRAF/MEK and anti-PD-1 treatment resistance, respectively.…”
Section: Genomic Analysis Of Metastatic Melanoma In An Adult With Giamentioning
confidence: 99%